FÍSICA PARA TODOS: UM EXPERIMENTO SOBRE CORES - DUARTE PEREIRA , YGOR; ROBERTO CONTRI HANKE , LUIZ; MEINCKE EICKHOFF , JULIANA; ADELAR TONIAZZO , NELSON; FERNANDO SAUTHIER , LUÍS; AFONSO SCHMIDT , PEDRO (Salão do Conhecimento, 2021)
Trabalho realizado pelo projeto de extensão Física para Todos